Structural, morphological and vibrational properties of Li4Ti5-xNbxO12 anode materials - D. Vijaya Lakshmi; B. Vikram Babu; A. Rama Krishna; M. Sushma Reddi; M.K. Raju; B. Sathish Mohan; B. Sridhar; P.V. Lakshmi Narayana (Materials Science for Energy Technologies, 2022)
The spinel structured chemical composition of Li4Ti5-xNbxO12 (0 ≤ x ≤ 0.1) anode materials are manufactured by solid state process. An organized exhibition of the outcomes of the structural, morphological and vibrational bonding nature of the negative electrode materials are investigated via the thermal studies, XRD, SEM with EDS and FT-IR. The detected peaks of diffraction are in absolute concurrence with the ordered Li4Ti5O12 (LTO) cubic structure exactly fitting to the Fd3m group of the spinel class. This result could indicate that the Nb element is totally inserted into the lattice of the base material. The grain sizes of niobium doped materials are large above the base material (LTO) and range around 1 μm in size. The FT-IR spectra are put to use to illustrate vibrational modes about the stretching and bending of various functional groups and also thereby confirm the spinel structure of the anode materials.